MEMAHAMI CORAK DAN METODE PENAFSIRAN TAFSIR SYIAH : (Kajian Terhadap Tafsir Al-Qummi dan Tafsir Al-Mizan) - Mutiara Ramadhani; Kerwanto; Putri Hafizatul Aini (LPPM STAI Nida El-Adabi, 2024)
This study aims to understand the patterns and methods of Qur'anic interpretation in the Shi'a tradition through the analysis of two major works, namely Tafsir Al-Qummi and Tafsir Al-Mizan. The main focus of this research is to identify the problems associated with the interpretative approaches employed by these two exegetes, particularly how their methods shape a distinctive understanding of the Qur'an. The study seeks to answer questions regarding the patterns and methods of these two tafsir works and their contributions to enriching the understanding of the Qur'an from a Shi'a perspective. Furthermore, the study highlights the significance of Shi'a exegesis, especially Tafsir Al-Qummi as a classical work and Tafsir al-Mizan as a modern interpretation. In offering a unique perspective, the Shi'a approach to tafsir emphasizes the central role of Ahl al-Bayt as the primary authority in understanding the Qur'an. Through the analysis of these two tafsir works, this study aims to demonstrate how the Shi'a tradition of Qur'anic exegesis not only expands interpretative methods but also provides profound insights into the relationship between the sacred text and Shi'a theological doctrine.